DESIGN OF A CANCER HOSPITAL WITH A BIOPHILIC APPROACH IN MANADO: Perancangan Rumah Sakit Kanker Dengan Pendekatan Biofilik Di Manado - Poka, Imanuel Happy; Suharto, Moh Fachruddin; Harimu, Debbie A. J (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2023)
The design of a cancer hospital in Manado is a design that aims to address the increasing number of cancer patients and the psychological problems of cancer patients in Manado through the relationship between humans and nature in the theme of biophilic architecture. WHO noted that there were 4.8 million cases of death due to cancer in Indonesia in 2018[4], and in Manado there was an increase from 1.4/1000 to 1.7/1000 from 2017 to 2018[6]. Cancer patients themselves according to Kübler-Ross in his book On Death and Dying 1969 will have difficulty facing death through 5 stages which is called the Kübler model[1]. In Manado itself, especially in serving cancer patients, they are still focusing on clinics in public hospitals due to the unavailability of a special cancer hospital.The method used in this design is design experiment, namely by testing design ideas through comparison or combining design ideas based on the strengths and weaknesses of each design idea, with the aim of obtaining the best design idea. The data collected in this design were obtained through surveys, observations, comparative studies, and literature studies where this data refers to the opportunities and threats of each topic being analyzed.Based on this design, it was found that the Manado Cancer Hospital is a special cancer hospital with the concept of "Therapeutic Forest", where this concept is a modification of the therapeutic garden concept which focuses on helping the patient's physical and psychological healing process through the arrangement of typical forest plants with accents of therapeutic plants on the inside and outside the building.. This Cancer Hospital is type A with 465 beds which are divided into 4 classes, namely class 3,2,1 and VIP, with facilities according to Appendix PERKEMENKES No. 30 years 2019[6]. This hospital is located on Jl. Kayu Bulan, Malalayang Satu, Kec.Malalayang, City of Manado, Pro. North Sulawesi where this location is an area for strengthening and developing hospital facilities based on Manado City Regional Regulation No.1 Article 50 paragraph 3 [7].